Effects of Earthquake on Behavior Characteristics of Fault Gouge in Time-History Analysis of Slope - Seong-Woo Moon; Hyeong-Sin Kim; Yong-Seok Seo (Advances in Materials Science and Engineering)
A time-history analysis, based on the finite element method, was performed to identify the behavior of a slope containing fault gouge during earthquakes. Input seismic waves were obtained from earthquake data measured in Korea, with five earthquakes (M3.0, M3.9, M5.1, M5.4, and M5.8) to analyse the magnitude effects. The acceleration effects indicate approximately 50%–110% residual shear strain depending on the acceleration fluctuation within the coda wave section after the maximum acceleration was reached. This indicates that the permanent deformation due to the earthquake will remain because the ground is an elastic-plastic material. The magnitude effects also indicate that both the maximum shear stress and strain increase simultaneously as the magnitude increases and as the maximum acceleration tends to increase with increasing magnitude. However, both the cumulative and maximum accelerations should be considered when assessing slope stability since both the maximum shear stress and strain are affected by these two accelerations. Analysis of the presence or absence of fault gouge indicates that the shear strain could be concentrated on fault gouge, which is easily deformed or destroyed by shear strain.